PELAKSANAAN KEWAJIBAN SEBAGAI PENGUSAHA KENA PAJAK OLEH PT CAHAYA PETRINDO BERSAMA JAKARTA TAHUN 2014 - Krisna Hidajat; Yanuar Adi Putra; Kiki Amaliya (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2015)
Value Added Tax (VAT) is a tax on the consumption of goods and services in the Customs Area that is needed to purchase production and distribution lines. PT Cahaya Petrindo Bersama is a company that has been confirmed as a Taxable Person for VAT purposes that requires Taxable Entrepreneurs in accordance with applicable tax regulations. The obligation of PT Cahaya Petrindo Bersama as a Taxable Person for VAT purposes is to impose a Collection, Calculation, Deposit and Report on Value Added Tax. Based on the discussion above, the purpose of the above research to discuss the implementation of the Obligations as Taxable Entrepreneurs by PT Cahaya Petrindo Bersama Jakarta 2014 is in accordance with the applicable tax regulations. From the results of the examination, it can be denied that PT Cahaya Petrindo Bersama Jakarta has made an agreement as a Taxable Person for VAT purposes in accordance with the applicable tax laws in Indonesia.